Multicomponent Theories of Hypnotizability: History and Prospects. Issue 1 (2nd January 2021) - Sadler, Pamela; Woody, Erik Z.
ABSTRACT: This review addresses multicomponent theories of hypnotizability by focusing on 3 important exemplars from the history of hypnosis research: E. R. Hilgard's (1965) Hypnotic susceptibility ; R. E. Shor's (1962) Three dimensions of hypnotic depth ; and T.X. Barber's (1999) A comprehensive three-dimensional theory of hypnosis . Taken together, they illustrate the variety of hypnotic phenomena examined in research – overt responses, subjective experiences, and underlying processes – and the ways in which evidence about each has implied the existence of multiple underlying components. Particularly highlighted are the different ways in which the theories conceptualize the joint contribution of multiple individual differences. Also covered is relevant later work by other researchers as well as important issues remaining to be resolved.